(untitled) (Nigerian Journal of Technology, 2024)
Multiple Input Multiple Output (MIMO) wireless systems offer substantial capacity gains over conventional wireless channels, making them well-suited for future high-speed wireless communications. However, ensuring high Quality of Service (QoS) for users in terms of signal quality, data speed, and reliability are some of the challenges of 5G wireless cellular networks. However, the effect of users’ mobility potentially may result in significant inter-beam interference, which increases the probability of outage in a Multi-User-MIMO (MU-MIMO) system. Although several studies have been carried out to mitigate the probability of outage, most of the studies either considered the impact of user mobility or User Equipment (UE) stationarity in determining outage performance or have used methods with high computational complexity that ignore one or both inter-beam interference and interference from the mobile UEs. This paper presents a model that minimizes the outage probability in the downlink of both mobile and stationary UEs in an MU-MIMO system. This proposed model to mitigate the outages encountered by mobile UEs in different scenarios: when a single UE is mobile when half of the UEs are mobile, and when all UEs are mobile within the proposed MU-MIMO system. These scenarios are assessed within a defined time frame to gauge the extent to which they reduce outage probability and enhance the spectral efficiency of the MU-MIMO system. Simulation results showed that the probability of outage in a discrete time frame and for UEs that are mobile in a discrete-time frame increased as the density of M increased. However, the proposed model minimized the probability of outage and improved the spectral efficiency in comparison to existing systems.